92 Engaging patients and parents to improve mental health for youth with systemic lupus erythematosus. (April 2019) - Knight, Andrea M; Fawole, Oluwatunmise; Reed, Michelle; Faust, Lauren; Rubinstein, Tamar; Harris, Julia; Hersh, Aimee; Onel, Karen; Lawson, Erica; Ardalan, Kaveh; Morgan, Esi; Paul, Anne; et al.
Abstract : Background: Mental health conditions are common in youth with systemic lupus erythematosus (SLE), yet intervention strategies are understudied. We used a patient-engaged approach to investigate the mental health needs of youth with SLE. Methods: An anonymous online survey examined beliefs and experiences with mental health for youth with SLE. Eligible youth ages 14–24 years had a diagnosis of SLE and reported specific treatment for the condition. Parents of youth 8–24 years meeting the above criteria were also eligible to participate. The survey was developed in collaboration with patient and parent advisors, the Childhood Arthritis and Rheumatology Research Alliance (CARRA), and the Patients, Advocates, and Rheumatology Teams Network for Research and Service (PARTNERS). Participants were recruited through the Lupus Foundation of America and CARRA clinics. We tabulated youth responses for i) self-reported prevalence of mental health problems, categorized into mutually exclusive clinician-diagnosed disorders and self-diagnosed symptoms, and ii) mean Likert ratings (0=low, 4=high) for the impact of disease related-factors on their mental health. We also compared youth and parent responses using regression models to examine comfort level with potential mental health providers. Results: 102 respondents included 59 patients (58%) and 43 (42%) parents. Youth had a mean age of 20.9 (standard deviation, SD=3.4) years, and mean disease duration of 6.9 (SD 4.0) years. History of a mental health problem was reported by 21 youth (36%), of which 66% said that their rheumatologist was unaware. Clinician-diagnosed anxiety was reported by 19%, depression by 12%, and adjustment disorders by 19%; another 17%, 8% and 10% had self-reported symptoms of these disorders, respectively. Mean Likert ratings by youth indicated that disease aspects most impacting mental health were worry about disease impact on the future at 3.0 (SD 1.2), worry about having a flare at 2.9 (1.2), and worry about medication side effects at 2.8 (1.3). Youth and parents felt most comfortable discussing mental health concerns with rheumatologists and primary care providers, and least comfortable with social workers and school counselors (figure 1 ). Conclusions: Youth with SLE have high rates of diagnosed and undiagnosed mental health problems, which are impacted by their disease. Mental health intervention strategies in rheumatology settings may improve mental health education, screening and treatment for these youth. Funding Source(s): The Childhood Arthritis and Rheumatology Research Alliance